Comparative Analysis of Selected Concrete Mix Design Methods Based on Cost-Effectiveness - Abebe Demissew (Advances in Civil Engineering)
Concrete is an amalgamated material that is composed of coarse granular materials embedded in a hard matrix of material that fills the void among the aggregate particles and binds them together. Concrete ingredients have to be properly classified and proportioned to build a mix that will be economical as well as meet the minimum requirements of functionality, safety, and economics. For this, there should be appropriate proportioning or mixing methods to arrive at the right combination of ingredients for making concrete according to the given specifications. Due to this, this study was intended to conduct a comparative analysis among selected concrete mix design methods, American Concrete Institute (ACI), British Department of Energy (DOE), Ethiopian Building Code of Standards (EBCS), and Indian standards (IS), by using experimental investigation for normal concrete production, focusing on cost-effectiveness. The concrete ingredients’ physical properties were compared as a requirement, and concrete mechanical properties were examined as per the method of concrete mix design on the 7th, 14th, and 28th days of curing. The experimental result of compressive strength for those selected concrete mix design methods with the 7th, 14th, and 28th ages has fulfilled the desire for concrete strength. However, on the 28th day of curing, compressive strength results of ACI, DOE, EBCS, and IS methods were achieved at 133.68%, 121.04%, 124.56%, and 121.04%, respectively. On the one hand, regarding the material of concrete consumption, the EBCS, DOE, and ACI methods were cast-off in an excess amount (52.2 kg/m3, 40 kg/m3, and 20 kg/m3) of cement, respectively, concerning the IS method. But the IS method was consuming 300 kg of cement per m3 of concrete. Finally, it is concluded that the result of the compressive strength test after 28 days showed that the specimens prepared using the mixing proportions obtained from the ACI standard met the extreme compressive strength requirement more than the other methods. On the other hand, the ACI, DOE, and EBCS methods are the most expensive to absorb an excessive quantity of cement when compared to the IS method. However, the overall result showed that the concrete designed as per the IS method is relatively easy to work with and cost-effective for developing countries such as Ethiopia for the production of normal grade concerts.